2021
DOI: 10.3390/brainsci11101259
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of Sleep Disorders in Children: A Narrative Review

Abstract: Sleep is a universal, highly preserved process, essential for human and animal life, whose complete functions are yet to be unravelled. Familial recurrence is acknowledged for some sleep disorders, but definite data are lacking for many of them. Genetic studies on sleep disorders have progressed from twin and family studies to candidate gene approaches to culminate in genome-wide association studies (GWAS). Several works disclosed that sleep-wake characteristics, in addition to electroencephalographic (EEG) sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 195 publications
(240 reference statements)
0
6
0
Order By: Relevance
“…3B ). We found that chronotype and insomnia played a predominant role in these genetic effects shared between sleep and organ structures and functions, which may be related to the extensive involvement of the loci in the regulation of circadian rhythms 135 . Genes associated with circadian rhythms were intricately linked to the underlying mechanisms that govern fundamental biological processes for human health, spanning multiple organs 50 .…”
Section: Discussionmentioning
confidence: 82%
“…3B ). We found that chronotype and insomnia played a predominant role in these genetic effects shared between sleep and organ structures and functions, which may be related to the extensive involvement of the loci in the regulation of circadian rhythms 135 . Genes associated with circadian rhythms were intricately linked to the underlying mechanisms that govern fundamental biological processes for human health, spanning multiple organs 50 .…”
Section: Discussionmentioning
confidence: 82%
“…However, those studies have not described a later but in fact an earlier chronotype (earlier bed and waking times) in young adults and adolescents born preterm, especially in those born SGA (Björkqvist et al, 2014,2020 Hibbs et al, 2014). This earlier chronotype may reflect developmental influences, as well as genetic alterations and/or parenting styles, and may be protective for later mental and physical health (Hibbs et al, 2014; Mainieri et al, 2021). Based on these findings, the association of birth size and social jetlag would have been expected in the opposite direction as observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Sudden infant death syndrome (SIDS) is the sudden and unexpected death of a healthy child under one year of age, usually during sleep. The cause of SIDS is still unknown, but many risk factors have been identified, including prematurity [ 93 , 94 , 95 , 96 , 97 ].…”
Section: Nts In the Neonatal Periodmentioning
confidence: 99%